Importance of viruses and Legionella pneumophila in respiratory exacerbations of young adults with cystic fibrosis. Issue 2 (February 1984) - Efthimiou, J; Hodson, M E; Taylor, P; Taylor, A G; Batten, J C
Abstract : From January to April 1980 46 young adults with cystic fibrosis were studied for evidence of infection with a wide variety of microorganisms, including viruses and Legionella pneumophila. Two groups of patients were investigated: a "deteriorated" group of 24 patients who had experienced an increase in lower respiratory tract symptoms and fall in lung function values in the course of one month before the start of the study and a "stable" group of 22 patients with no such deterioration. All serological tests were repeated at one month and then one year after the beginning of the study. A fourfold rise in titres of antibodies to various viruses, Mycoplasma pneumoniae, and Coxiella burnetii was obtained in seven (29%) of the deteriorated group but in only one (4.5%) of the stable group (p less than 0.05). One other patient showed a fourfold rise in L pneumophila antibody titre (on the basis of the indirect fluorescent antibody test), which was accompanied by a respiratory illness consistent with legionnaires' disease. Eight of the 46 patients (17.4%) had demonstrable titres of antibody against L pneumophila (1/32 or above).